2011
DOI: 10.5539/ijbm.v6n5p28
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance Mechanisms and Firm Efficiency

Abstract: This paper uses technical efficiency to measure the performance impact of internal corporate governance mechanisms. Specifically, it analyzes how the size, leadership and composition of the board of directors together with external shareholders can be structured to enhance a firm's technical efficiency. The study utilizes an unbalanced pool of manufacturing firms in sixteen countries and offers support that active large external shareholders' who commit credible signals to minority investors of firms that have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…While other groups emphasize the smaller size of the board, they have established that the smaller size of the board is more effective in decision-making, so it increases efficiency and leads firms to a higher level [55][56][57]. Many studies have taken the size of the board as exogenous and have established a positive influence on the return on assets, share prices and overall performance of the firms using OLS regression, fixed and random effect model, and DAE analysis for efficiency [58][59]. A recent study on the size of the board using the panel regression model found that the size of the board increases the financial performance of listed companies in emerging South Asian markets [60].…”
Section: Size Of the Board Of Directorsmentioning
confidence: 99%
“…While other groups emphasize the smaller size of the board, they have established that the smaller size of the board is more effective in decision-making, so it increases efficiency and leads firms to a higher level [55][56][57]. Many studies have taken the size of the board as exogenous and have established a positive influence on the return on assets, share prices and overall performance of the firms using OLS regression, fixed and random effect model, and DAE analysis for efficiency [58][59]. A recent study on the size of the board using the panel regression model found that the size of the board increases the financial performance of listed companies in emerging South Asian markets [60].…”
Section: Size Of the Board Of Directorsmentioning
confidence: 99%
“…Prior studies concentrated on two factors of board characteristics namely size of the board and board independence. The present research adds board meeting to these characteristics (Al Manaseer et al, 2012;Kang & Kim, 2011;Li et al, 2012;Nanka-Bruce, 2011;Obiyo & Lenee, 2011).…”
Section: Board Meeting and Firm Performancementioning
confidence: 99%
“…The attention of academic literature has been on various board attributes influence on firm performance ( Saibaba and Ansari, 2011 ; Dalton and Dalton, 2011 ; Nanka-Bruce, 2011 ; Rebeiz, 2015 ; Uwuigbe et al., 2018 ). These board attributes examined by previous researchers were board size, board independence, board diversity, board composition etc.…”
Section: Introductionmentioning
confidence: 99%